ВОПРОСЫ ВСКАРМЛИВАНИЯ ДЕТЕЙ С ПИЩЕВОЙ АЛЛЕРГИЕЙ - article editorial (Педиатрическая фармакология)
From the Editor: Dear Colleagues! It is becoming a tradition to acquaint you with the most relevant issues discussed at scientific conferences and congresses held both in our country and abroad. This time we want to discuss a conference "Movement against allergy" organized by the European Academy which was held in Prague on 7-8 March 2008 and was dedicated to food allergies in children.